2022
DOI: 10.1186/s12936-022-04147-0
|View full text |Cite
|
Sign up to set email alerts
|

Fast detection and quantification of Plasmodium species infected erythrocytes in a non-endemic region by using the Sysmex XN-31 analyzer

Abstract: Background Due to increased travel from endemic countries, malaria occurs more frequently in non-endemic regions. It is a challenge for diagnostic laboratories in non-endemic countries to provide reliable results, as experience of staff is often limited to only a few cases per year. This study evaluated the diagnostic accuracy of the fully automated Sysmex XN-31 malaria analyzer in a routine diagnostic setting in a non-endemic region was evaluated. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Thus, the LoD (limit of detection) of the LM mode of the XN-31p could be much lower than the LoQ value defined by the company. This result is consistent with a recent report [ 12 ] that estimated LoD and LoQ values for the LM mode of the XN-31 using cultured P. falciparum . Recently, asymptomatic malaria cases with low-density parasitaemia have been discussed as potential reservoirs for transmission in endemic areas [ 16 18 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Thus, the LoD (limit of detection) of the LM mode of the XN-31p could be much lower than the LoQ value defined by the company. This result is consistent with a recent report [ 12 ] that estimated LoD and LoQ values for the LM mode of the XN-31 using cultured P. falciparum . Recently, asymptomatic malaria cases with low-density parasitaemia have been discussed as potential reservoirs for transmission in endemic areas [ 16 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…The XN-31p means a prototype device before the release of the XN-31 commercially which has the same physical characteristics, hardware configuration, and reagent composition as does the XN-31p. For the XN-31p and the XN-31, their excellent performance as malaria diagnostics in clinical settings were also suggested in recent reports respectively [11][12][13].…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Few of these diseases/conditions are sickle cell disease, beta thalassemia, haemochromatosis premature newborns, etc. [13]. Though these individual diseases/conditions were not evaluated in the present study, it is possible that few of the samples in the present study cohort of ‘clinical samples’ had one of these underlying disease conditions, triggering false‐positive results in XN‐31.…”
Section: Discussionmentioning
confidence: 96%
“…New advances based on fluorescence flow cytometry have shown that the Sysmex XN-31 device can determine the Plasmodium species and quantify parasites in blood. However, it can generate false positive results in case of abnormal erythrocytes cell morphology and the device was tested in a non-endemic region ( Khartabil et al, 2022 ).…”
Section: Malaria Diagnosismentioning
confidence: 99%